Analisis Pengaruh Atribut Religius dalam Konten Promosi di Media Sosial Terhadap Behavioural Intention Konsumen Muslim - Primaputri, Rizkia Amalia; Alversia, Yeshika (UI Scholars Hub, 2023)
This study investigates the effect of religious-related attributes in social media promotion materials towards Muslim consumers’ behavioural intention, with consumer’s offensiveness mediating. Theories are applied to a case where Hanamasa Indonesia’s promotion materials were treated with skeptical e-WOMs since a customer revealed her experience was contrast to what appears visually and audibly on the restaurant’s social media posts. This quantitative study utilized 204 samples in a SEM (structural equation modelling) analysis and resulted: 1) visual attributes cause negative e-WOM indirectly, 2) consumer’s offensiveness mediates visual attributes on social media promotion materials to cause negative e-WOM, 3) consumer’s responsiveness mediates visual attributes on social media promotion materials to their offensiveness and 4) how consumers perceive the importance of Halal logo prevents them from getting offended.